Evaluation of an Ultra-Sensitive PCR Assay for Porcine Mitochondrial Cytochrome b Detection under Laboratory Conditions - Larasati, Dita Umi Rosidah (Halal Science, 2025)
Food adulteration with porcine derivatives poses significant challenges to halal authentication and consumer protection. Sensitive molecular detection methods are therefore required to support food authenticity assessment. This study aimed to evaluate the analytical sensitivity of a PCR-based assay targeting porcine mitochondrial cytochrome b (cyt b) DNA. Genomic DNA was isolated from porcine intestine, adipose tissue, liver, blood, and muscle using the Wizard® Genomic DNA Purification Kit, quantified by spectrophotometry, and amplified using species-specific primers. Analytical sensitivity was assessed using stepwise serial dilutions of porcine DNA under controlled laboratory conditions. The extracted DNA showed acceptable purity for PCR amplification, with A260/A280 ratios within the expected range. PCR amplification produced detectable cyt b bands across a wide range of nominal DNA dilution levels, indicating high analytical sensitivity of the assay. The detection limit was determined operationally based on consistent visual band detection following agarose gel electrophoresis. These findings demonstrate the potential of the optimized PCR assay as a sensitive molecular tool for porcine DNA detection, with prospective applicability for halal authentication and food safety monitoring pending further validation in complex food matrices.